Like or follow: Analysis of the communication of Corporate Social Responsibility practices through Social Media - Gómez Vásquez, Lina (2013)
Corporate Social Responsibility (CSR) can be defined as a responsible way of doing business and the impact these operations have in the economy, the society and the environment. Nowadays, companies use different avenues to communicate CSR initiatives. Social Media platforms are one of the important resources to communicate CSR. This paper performs an empirical analysis of frequency, content, and feedback of CSR messages presented on social platforms (Facebook and Twitter) of 50 companies from the Fortune Magazine. Results showed that in spite of the great resources available for CSR online communication, companies are still in its infancy in promoting a two-way communication process. In order to resolve this problem, this paper proposes a theoretical framework for CSR communication through social media.